NEUROPLASTICITY AND DIGITAL TOOLS IN LIFELONG LEARNING: COGNITIVE CHALLENGES AND OPPORTUNITIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Neuroplasticity plays a crucial role in lifelong learning (LLL), particularly in supporting cognitive adaptability and resilience in older adults. The integration of digital learning tools has introduced new opportunities for enhancing memory, attention, and cognitive flexibility. This study explores the impact of gamification, adaptive learning platforms, and AI-driven education on neuroplasticity, emphasizing their role in maintaining cognitive functions and fostering engagement. The research examines how digital learning environments, including language apps (e.g., Duolingo), MOOCs (e.g., Coursera, Khan Academy), and virtual simulations, contribute to cognitive stimulation. While these tools provide increased accessibility and engagement, challenges such as digital stress, motivation fluctuations, and information overload remain key concerns. The study further investigates how self-regulation strategies and structured learning environments can optimize digital education for older learners. By analyzing expert insights, case studies, and existing research, this study proposes recommendations for improving digital learning experiences tailored to cognitive aging. The findings contribute to ongoing discussions on lifelong learning, offering strategies to support cognitive health and maximize the potential of digital education for an aging population.